2008
DOI: 10.1111/j.1365-2354.2007.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the addition of video-based education for patients receiving standard pre-chemotherapy education

Abstract: Preparing cancer patients and their families for chemotherapy treatment is difficult. The challenge lies in finding ways to promote self-care and improve their ability to recall instructions. The aim of this study was to evaluate the usefulness of an educational video with regard to patients' ability to recall and report side effects of treatment. Patients referred for adjuvant chemotherapy for breast and colorectal cancer were randomized to receive standard pre-chemotherapy education or standard education plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 22 publications
4
31
0
2
Order By: Relevance
“…Research shows that (online) video modeling can facilitate patient understanding, improve self-care, and increase patient centeredness [43,44]. In addition, Kinnane and Thompson showed that the inclusion of a video to patient education surrounding chemotherapy improved information recall and the reporting of treatment-related symptoms [45]. In accordance with the self-management education theory of Lorig and Holman, the use of video examples appears to provide patients with the tools and (communication) skills to solve, handle, or act during certain situations [46].…”
Section: Resultsmentioning
confidence: 99%
“…Research shows that (online) video modeling can facilitate patient understanding, improve self-care, and increase patient centeredness [43,44]. In addition, Kinnane and Thompson showed that the inclusion of a video to patient education surrounding chemotherapy improved information recall and the reporting of treatment-related symptoms [45]. In accordance with the self-management education theory of Lorig and Holman, the use of video examples appears to provide patients with the tools and (communication) skills to solve, handle, or act during certain situations [46].…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with previous studies that inclusion of video to standard chemotherapy education improves retention of information regarding management of predictable chemotherapy side effects and reporting of treatment-related symptoms. [15]…”
Section: Discussionmentioning
confidence: 99%
“…[14] However, Kinnane and Thompson[15] concluded that patients who viewed the video in conjunction with standard chemotherapy education improve retention of information regarding management of predictable chemotherapy side effects and reporting of treatment-related symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Cette Ă©ducation se fera pendant le colloque singulier soignant-soignĂ© et pourra ĂȘtre complĂ©tĂ©e et non remplacĂ©e par des documents Ă©crits ou des vidĂ©os [17].…”
Section: Application De L'etp Dans Le Cancer Du Seinunclassified